2023
DOI: 10.2147/phmt.s396854
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Rheumatic Heart Disease Related Complications in Pediatric Patients at Tertiary Hospital, Addis Ababa, Ethiopia

Abstract: Introduction Rheumatic heart disease continues to be a public health problem worldwide. In developing countries such as Ethiopia where rheumatic heart disease is endemic, most of the patients present with complaints related to complications including heart failure, arrhythmias, pulmonary hypertension, stroke, systemic embolic events and infective endocarditis. Objective To identify the types and magnitude of complications in pediatric patients with rheumatic heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Severe acute malnutrition and severe anemia were common comorbidities in both RHD groups, consistent with a tertiary hospital study in Ethiopia that found malnutrition in 50.7% of patients [12]. At admission, 89.7% of patients had class IV heart failure, with comparable gures between the two groups.…”
Section: Discussionsupporting
confidence: 87%
“…Severe acute malnutrition and severe anemia were common comorbidities in both RHD groups, consistent with a tertiary hospital study in Ethiopia that found malnutrition in 50.7% of patients [12]. At admission, 89.7% of patients had class IV heart failure, with comparable gures between the two groups.…”
Section: Discussionsupporting
confidence: 87%
“…The most common complication encountered was heart failure (61.4%), followed by pulmonary hypertension (59.3%), malnutrition (50.7%), and infectious endocarditis (3.6%). 3 …”
Section: Discussionmentioning
confidence: 99%
“… 2 Despite the fact that patients with RF/RHD require early medical attention and follow-up, a significant number of patients in developing nations tends to present with debilitating complications such as heart failure, pulmonary hypertension, and arrhythmias. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 A similar study done by Desta et al also reported that 136 (97.1%) of patients had mitral regurgitation, which was significantly higher than our study findings. 28 This variation could be due to differences in study design and sample size.…”
Section: Discussionmentioning
confidence: 99%